Research Progress on Models, Algorithms, and Systems for Remote Sensing Spatial-Temporal Big Data Processing - Yang Liu; Lanxue Dang; Shenshen Li; Kun Cai; Xianyu Zuo (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2021)
With the rapid development of high-resolution earth observation systems, the data processing, algorithm design, and system development of remote sensing spatial-temporal big data (RS-STBD) have gradually become the bottleneck problems in the application and development of earth observation system. The research on the model, algorithm, and system of RS-STBD processing involves complex scientific problems, technical bottlenecks, and inconstant requirements of engineering applications. This article summarizes the data type and processing theory model of RS-STBD, the high-performance algorithm design based on cloud service and intelligent computing, and the architecture design and engineering development methods of the complex remote sensing application system. Furthermore, the existing problems in the current research are analyzed, and the related solutions are given. Finally, the future development trend of scientific exploration, technical research, and application development of RS-STBD has prospected.